PELATIHAN KADER POSYANDU AISYIYAH KARENGLEWAS KIDUL DALAM MENDETEKSI KEJADIAN DIABETES MELLITUS LANSIA - Izka Sofiyya Wahyurin; Ajeng Dian Purnamasari; Izzati Nur Khoiriani (Universitas Jenderal Soedirman, 2021)
The role of health care providers is very important in promoting and preventing efforts to improve the quality of life of the elderly , especially in the prevention and management of degenerative diseases such as Diabetes mellitus. However, in the development of the Posyandu Lansia, health care providers have many limitations, such as a lack of skills in detecting the incidence of Diabetes mellitus in the elderly. Through the training of Posyandu Aisyiyah Karanglewas Kidul health care providers to detect the incidence of Diabetes mellitus in the elderly when using an independent blood sugar control tool, the skills of cadres before and after training have increased. The results showed that the training had an effect on improving the skills of health care providers in using the independent blood sugar check tool by 40.3%. By improving the skills of these cadres, it is hoped that the cadres of the Posyandu Lansia can independently check their blood glucose levels so that diabetes mellitus at Aisyiyah's Posyandu can be prevented and handled.